2021
DOI: 10.21608/edj.2020.51707.1371
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Giomer Versus Sodium Fluoride Varnish for Management of Hypersensitivity: Randomized Control Trail

Abstract: Aim: to assess the clinical effectiveness of Giomer varnish in comparison to sodium fluoride in reducing dentin hypersensitivity. Methodology: Using a Split mouth design, 66 participants (132 teeth) of the outpatient clinic in the Faculty of dentistry, Cairo University, were enrolled. Each participant should have at least two sensitive teeth in different sides of the same jaw, with a visual analogue scale score two or more. Teeth were examined by using different stimuli: Evaporative, thermal and tactile stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Similar results were found in a clinical study comparing PBC and BiFluorid 10 for reducing DH, where PBC showed a significant difference only in the evaluation conducted 1 week after application [ 37 ]. The fact that the reduction in DH does not occur immediately after the application of PBC may be related to its mechanism of action, which occurs gradually when in contact with oral fluids, by binding ions to collagen fibers, while fluoride and strontium bind to apatite present in the dental structure, improving its resistance to acid attack [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were found in a clinical study comparing PBC and BiFluorid 10 for reducing DH, where PBC showed a significant difference only in the evaluation conducted 1 week after application [ 37 ]. The fact that the reduction in DH does not occur immediately after the application of PBC may be related to its mechanism of action, which occurs gradually when in contact with oral fluids, by binding ions to collagen fibers, while fluoride and strontium bind to apatite present in the dental structure, improving its resistance to acid attack [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…The results obtained in this study were significant for the management of DH at all proposed time points, and they particularly stood out in the PDR and control groups. It should be mentioned that PBC is a promising agent that has demonstrated its long-lasting effect in managing DH due to its mechanism of ion release and precipitation, aiding in remineralization and obliteration of dentinal tubules, as observed after 12 months of application in this study, as well as in the Control group [ 37 ]. This is attributed to the characteristics of SBU, with the presence of 10-MDP, which stabilizes in an aqueous medium and chemically bonds with dentin, obliterating the dentinal tubules [ 32 ].…”
Section: Discussionmentioning
confidence: 85%
“…Most fluoride 2 of 11 varnishes comprise 5% sodium fluoride; nevertheless, the manufacturer may have various fluoride concentrations and forms [5]. Sodium fluoride varnish is regarded as the gold standard desensitizing substance [6]. Bifluorid 10 (5% sodium fluoride and 5% calcium fluoride) adheres to the teeth and begins to provide instant protection from any damaging stimulus [7].…”
Section: Introductionmentioning
confidence: 99%